Blood Pressure and Early Mobilization After Total Hip and Knee Replacements: A Pilot Study on the Impact of Midodrine Hydrochloride. Issue 2 (April 2019) - Smits, Michael; Lin, Sandra; Rahme, Jessica; Bailey, Michael; Bellomo, Rinaldo; Hardidge, Andrew
Abstract : Background: Early mobilization is an important therapeutic goal after total knee replacement and total hip replacement. Orthostatic hypotension and orthostatic intolerance can impede mobilization. Midodrine hydrochloride, an orally administered vasoconstrictor, may improve blood pressure and diminish the prevalence of adverse mobilization events. Methods: We conducted a pilot change-of-practice study. Two cohorts, each comprising 10 patients managed with total knee replacement and 10 patients managed with total hip replacement, were managed with blood pressure-adjusted midodrine, which was administered 3 times daily for the first 72 hours postoperatively at either a low dose (2.5 or 5 mg) or a higher dose (5 or 10 mg). These patients were then matched with an equivalent preintervention cohort of patients. Results: The midodrine protocol was instituted effectively and with high compliance. Hypotension was uncommon across all groups, with the mean lowest systolic blood pressure ranging from 110 to 121 mm Hg. Moreover, adverse mobilization events were uncommon across all groups (prevalence, 9.6% in the control group, 5.6% in the low-dose group, and 2.9% in the high-dose group) (p = 0.046 for the high-dose group versus the control group). A midodrine dose of 10 mg generated a significant mean dose-related systolic blood pressure increase of 14 mm Hg at 2 hours after administration (p < 0.001). There were no significant differences between the groups in terms of mean systolic blood pressure, biochemical markers, or intravenous therapy administration. Conclusions: A dose of 10 mg was found to achieve a significant systolic blood pressure response at 2 hours after administration and, in patients who received higher-dose midodrine, adverse mobilization events appeared less common. Additional investigation with a blinded randomized controlled trial, utilizing 10 mg of midodrine 2 hours before mobilization, would be needed to confirm the efficacy of midodrine therapy. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.